NOVELET "BATU SANDUNG" KARYA RATNA INDRASW ARI IBRAHIM: PERJUANGAN SEORANG PEREMPUAN CACAT MERAIH KEBERHASILAN - Windiyarti, Dara (ATAVISME, 2008)
The aim of this paper is to reveal the internal conflict and struggle of Irina, the main character in novellete "Batu Sandung", one of the novelletes in Batu Sandung created by Ratna Indraswari Ibrahim. The main reason of Irina internal conflict emergence is the surrounding reaction on her physical defect. Her success is achieved through her struggle in exploring her surround. The discussion of the main character's internal conflicts and struggle is using Alfred Adler's individual psychology theory/approach. This paper reveals: (1) Irina's internal conflict; and (2) Irina's struggle to reach her success through: (a) gaining the strenght from the inside, (b) developing subjective conviction, (c) developing social interest, and (d) gaining creative self strength.